Cadmium concentrations in recent snow and firn layers in the Canadian arctic - Gregor, D. J.; Nriagu, Jerome O.; Lawson, G. S. (Bulletin of Environmental Contamination and Toxicology, 1994)
Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/47997/1/128_2004_Article_BF00195499.pdf